Implementing patience in islam for young entrepreneurship - Syaiful Hadi; Sulaiman (At Turots: Jurnal Pendidikan Islam, 2024)
Self-employment is the new activity for young people. The existence of covid-19 and massive layoffs is a boon for young people who work. With these problems, young people are motivated to carry out young entrepreneurial activities. However, beginners still experience various kinds of new problems in developing it. The concept of patience is one of the supports in dealing with these problems. Where young people are directed to focus on self-organisation so that their positive energy can provide solutions that can handle these problems. This research aims to find out the entrepreneurial motivation and the problems faced and their handling. The research method involved field studies and interviews with entrepreneurs and data was collected through participatory observation, field notes, and evaluation of concept understanding. The results showed that the implementation of patience for young entrepreneurs is very effective and able to provide solutions to any problems that occur.